Transport disadvantage and extracurricular activities. The example of secondary school students of the city of Zagreb. - Gasparovic, Slaven (My University, 2017)
Der Beitrag untersucht die Auswirkungen von Verkehrsnachteilen auf außerschulische Aktivitäten von Gymnasiasten der Stadt Zagreb.

Nowadays, transport disadvantage is outspread phenomenon. It can influence people's needs and opportunities. Young people are considered transport disadvantaged part of the society. Secondary school students are young people with a great need for mobility but still, their mobility is also limited. Their dependence on other people in the aspect of transportation and public transportation greatly influence their everyday lives. Important segment of young people's lives are extracurricular activities. The aim of this paper is to investigate the impact of transport disadvantage on extracurricular activities of secondary school students of the city of Zagreb. Particular emphasis is on the difficulties in accessibility of extracurricular activities and how transport influences these activities. Research was conducted using quantitative and qualitative methods. The data were obtained through questionnaire survey of 826 secondary school students of secondary schools of the city of Zagreb. In order to deepen the research, interviews were performed through eight focus groups. Data analysis revealed that almost half of secondary school students involved in extracurricular activities expressed the attitude of having difficulties with accessibility of extracurricular activities and that over half of secondary school students involved in extracurricular activities responded that transport had impact on these activities. Significant correlations between the attitude of problem existence with accessibility of extracurricular activities and travel time needed to reach them, as well as between travel time to extracurricular activities and attitudes on the impact of transport on these activities were found. The existence of students not able to participate in extracurricular activities because of transportation was determined. All the results were supported by states collected through focus group Research.
Keywords: Großstadt; Jugendlicher; Mobilität; Öffentlicher Verkehr; Erreichbarkeit